Euro area market reactions to the monetary developments press release - Jerome Coffinet; Sylvain Gouteron (European Central Bank (ECB), 2007)
Using intra-day data, we assess the impact of the press release on euro area monetary data on the different segments of the euro area yield curve. For this purpose, we estimate a relation between the “news” or “surprise” in the released data for annual M3 growth and the move in the interest rates for a time-window surrounding the press release. We find that the publication of monetary data has a statistically significant impact on interest rates with maturities ranging from 1 to 10 years, with the largest effect on the 1-2 year segment. Turning to the short end of the yield curve, since mid-2001 rates with maturities up to 6 months do not react much to the monetary developments press release. Our results suggest that market participants may look through short-term movements of annual M3 growth and focus instead on the trend rate of monetary expansion over the medium term when gauging the policy relevant signals.
Keywords: E43; E44; E52; E58; 330; high-frequency data; macroeconomic announcements; money growth; Eurozone; Geldmenge; Politische Kommunikation; Glaubwürdigkeit; Zentralbank; Wirkungsanalyse; Zinsstruktur; EU-Staaten